The Use of Video Subtitles to Increase Junior High School Students' Vocabulary Mastery: An Experimental Study - Rosida, Emy; Nugroho, Him’mawan Adi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The teaching and learning vocabulary still become one of concerns in English as Foreign Language study in Indonesia. It is a big deal since English is a foreign language and students do not encounter English in their daily life. It leads us to understand the importance of English as Foreign Language teachers' role in enriching students' vocabulary mastery. Video subtitles becomes one of popular media in EFL teaching. Many previous scholars have proofed the effectiveness of using video subtitles as the teaching media. Unfortunately, study focuses on the effect of video subtitles toward secondary school students especially 7th graders still need further exploration. This study aims to examine whether the video subtitles can be an effective teaching media for 7th graders. A quantitative research methodology implementing quasi-experimental research design for gathering data process and inferential statistic using t-test for analyzing data process are carried out in this study. The findings reveal that video subtitles are an effective teaching media for 7th graders in improving their vocabulary mastery.